Tinjauan Literatur: Regulasi Diri pada Mahasiswa Bekerja dalam Mencapai Keberhasilan Akademik - Firsty Oktaria Grahani; Anindito Aditomo; Lena Nessyana Pandjaitan (Fakultas Psikologi Universitas Pancasila, 2023)
Changes in social, economic, and cultural dynamics create a paradigm shift in the student experience in the modern era, many students choose to work while pursuing their studies in tertiary institutions. The ability to self-regulate is needed in order to be able to live all its dynamics in a balanced way. Self-regulation plays a role in several aspects, namely the ability to manage time and effort, planning and clear goals, the ability to control oneself while studying or working, increasing resistance to stress, the ability to face obstacles, the ability to manage one's own motivation, and so on. This literature review aims to examine the role of self-regulation in achieving academic success and career success in working students. The method used in data collection was a literature review found in journal databases, namely Google Scholar, Research Gate, and Science Direct in both English and Indonesian in 1,510 articles published over the last ten years. The results of the study found seven articles that examined the importance of the role of self-regulation in working students in achieving academic success and managing their careers well. The conclusion is that self-regulation is crucial for academic success, influenced by goal orientation and other factors.